Angioscopic findings 1 year after percutaneous coronary intervention for chronic total occlusion. Issue 1 (January 2023) - Fukuizumi, Isamu; Tokita, Yukichi; Shiomura, Reiko; Noma, Satsuki; Matsuda, Junya; Sangen, Hideto; Kubota, Yoshiaki; Komiyama, Hidenori; Nakata, Jun; Miyachi, Hideki; Tara, Shuhei; Shimizu, Wataru; et al.
Abstract: Background: Chronic total occlusion (CTO) is a high-risk factor for stent thrombosis, but little is known about the difference in neointimal healing between CTO and non-CTO lesions regarding implanted stents. We investigated factors affecting neointimal healing after stent implantation for CTO and non-CTO lesions using angioscopy. Methods: We retrospectively evaluated 106 stents in 85 consecutive patients between March 2016 and July 2020. Their average age was 68 ± 11 years, and participants (73 male and 12 female) underwent follow-up angiography and angioscopy 1 year after percutaneous coronary intervention (PCI). The stents ( n = 106) were divided into three groups according to the lesion status at the previous PCI: CTO ( n = 17), acute coronary syndrome (ACS) ( n = 35), and stable coronary artery disease without CTO or non-CTO ( n = 54). Results: The neointimal stent coverage grade was significantly lower in the CTO and ACS groups than in the non-CTO group (0.4 ± 0.5, 0.9 ± 0.8, and 1.4 ± 0.8, respectively, p < 0.001). Thrombi were significantly more frequent in CTO and ACS than in non-CTO (71 %, 51 %, and 15 %, respectively, p < 0.001). The yellow grade in CTO was comparable to that in ACS but significantly higher in CTO than in non-CTO (CTO vs. ACS vs. non-CTO 1.5 ± 0.7, 1.4 ± 0.6, and 0.9 ± 0.7, respectively, p = 0.007). Conclusions: Delayed healing occurs in stents implanted for CTO lesions. Longer dual-antithrombotic therapy may be beneficial. Graphical abstract: Unlabelled Image Highlights: This study suggests delayed healing of stents implanted for chronic total occlusion (CTO) lesions. Longer duration of dual-antiplatelet therapy (DAPT) may be beneficial for these patients. Delayed healing for stents implanted for acute coronary syndrome lesions. Extended DAPT may be useful in cases of percutaneous coronary intervention for CTO lesions.